ANALISIS PERKEMBANGBIAKAN TUMBUHAN SECARA VEGETATIF - Annisa Fitri; Yunita Sakila (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to provide a comprehensive explanation of the process, types, benefits, and advantages and disadvantages of vegetative reproduction in plants, both naturally occurring and assisted by humans. This study uses a literature review method, in which all data is collected from junior high and high school biology textbooks, scientific education journals, online articles, and teacher teaching modules. The information obtained was then analyzed and systematically organized to make it easily understandable for students and the general public. The results of the study indicate that vegetative reproduction is an effective method for plants to multiply without seeds. Naturally, this reproduction occurs through plant parts such as roots, stems, and leaves, for example in ginger, onions, or bananas. Artificially, humans utilize techniques such as cuttings, grafting, budding, layering, and rooting to accelerate the propagation of superior plants. Vegetative reproduction has advantages such as a faster process, plants that are identical to their parents, independence from seasonal constraints, and suitability for maintaining the quality of superior plants. However, this method also has drawbacks, including the inability to produce new variations, the risk of transmitting diseases from the parent to the offspring, and not all plants can be propagated using this method. This study concludes that knowledge about vegetative propagation is very important to be introduced early on because it is beneficial for agriculture, education, and daily life, especially in planting and gardening activities.